The SmartAG Partner: CCAFS East Africa Quarterly Newsletter, July - September 2015 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
As we look forward to a new climate agreement at the conclusion of the 21st sessions of the Conference of the Parties to the United Nations Framework Convention on Climate Change (UNFCCC-COP21) in Paris, France this December, we highlight progress made by countries to address climate change. Read about Kenya’s Intended Nationally Determined Contribution, submitted to the UNFCCC, which incorporates climate-smart agriculture. From Uganda, learn how and why the government is mainstreaming climate change into its agriculture plans and policies. In a commentary on SciDev.Net, we offer opinion on how the international dialogue on climate change needs to make agriculture integral to emerging agreements and programs.